Predicting aggressive collective action based on the efficacy of peaceful and aggressive actions. (1st July 2016) - Saab, Rim; Spears, Russell; Tausch, Nicole; Sasse, Julia
Abstract: We examine whether aggressive forms of collective action are predicted by their perceived efficacy and the perceived efficacy of peaceful collective action, and whether the two predictors interact. We present data from surveys examining support for and tendencies toward aggressive collective action among university students who are opposed to increases in tuition fees in Britain (Study 1) and support for suicide bombings against Israeli civilians among Palestinians during the Second Intifada (Study 2). Our results reveal an interaction between the efficacy of peaceful and aggressive collective actions: The more efficacious aggression is perceived to be, the greater its appeal and the less it is assuaged by the efficacy of peaceful action. This implies that (i) people may consider aggressive action whenever it works, even if peaceful action is efficacious, and (ii) people may consider aggressive action even when it seems unpromising, if peaceful action is not efficacious, in an apparent nothing‐to‐lose strategy.